2020
DOI: 10.1097/bot.0000000000001802
|View full text |Cite
|
Sign up to set email alerts
|

Taylor Spatial Frame or Reamed Intramedullary Nailing for Closed Fractures of the Tibial Shaft: A Randomized Controlled Trial

Abstract: Objectives: To compare a modern ring fixator [Taylor Spatial Frame (TSF)] and reamed intramedullary nailing (IMN) for the treatment of closed tibial shaft fractures. Design: Randomized controlled trial. Setting: Two university hospitals. Patients: Patients between 18 and 70 years of age surgically treated for an acute tibial shaft fracture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…To our knowledge, this is the first multicenter randomized clinical trial in the U.S. comparing modern external ring fixators to internal fixation for severe open tibial shaft fractures. Although there have been smaller randomized trials comparing external and internal fixation, those studies either did not examine modern external ring fixators or did not focus on severe open injuries 24-28 . The strengths of our trial include the multicenter randomized design with well-balanced treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first multicenter randomized clinical trial in the U.S. comparing modern external ring fixators to internal fixation for severe open tibial shaft fractures. Although there have been smaller randomized trials comparing external and internal fixation, those studies either did not examine modern external ring fixators or did not focus on severe open injuries 24-28 . The strengths of our trial include the multicenter randomized design with well-balanced treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…At 12 months, these disturbances were still present in 18% and 54% of patients in the transverse and longitudinal incision group, respectively (p < 0.001). A study comparing a Taylor Spatial Frame (TSF; Smith & Nephew) and reamed intramedullary nailing for the treatment of closed tibial shaft fractures found that the TSF group had less knee pain (VAS score of 0.5 [SD, 1.2] versus 2.4 [SD, 2.2] at 1 year; p < 0.001]) 21 . With increasing awareness of anterior knee pain after tibial nailing, new surgical techniques intended to address this issue have been described in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a good surgical effect requires continuous study and reflection. The application of TSF can solve the shortcomings of traditional HTO surgery [ 10 ]. It improves the accuracy of osteotomy through 3D preoperative planning.…”
Section: Discussionmentioning
confidence: 99%